المواقف بين القصة الانكليزية العربية الكردية القصيرة- دراسة مقارنة - - كريم, طاهر لطيف; نوشيروان, نيان (Sulaimani Journal for Humanities, 2000)
Here the situation is a work equation and a work feflection , and both of them will make the result . Short dtory is an examply of this work. It deals with the situation and determines the humanitarian situations including the work and is reflection with the result which create a new subject for the comparative Literature.